Experimentações e prática no ensino de química : construindo saber químico escolar a partir de uma aprendizagem significativa - LIMA, Diego Souza (2018)
The Teaching of Chemistry has traditionally been limited to mere reproduction of concepts, in which science becomes inaccessible to society. The scientific knowledge thus addressed is limited to scientific-academic, not exploring the ability of students to reflect as builders of knowledge, lacking meaning and applicability. This work was based on our internship experiences, carried out in the discipline of Chemistry and objective, in view of the refusal to Teach Chemistry, to discuss the realization of experiments and practical classes as ways to guide a meaningful learning in the discipline, besides reflecting on the role of the teacher as mediator of learning situations. In the course of the stages, we seek to carry out experiments and, given the different realities and specificities of the subjects involved, practical classes that, in treating students as constructors of their own learning, allowed us to mediate situations towards meaningful learning. Thus, when we consider that the teaching practice is built during the course of his career, we conclude with this work that the experiments and practical classes can guide the subjects involved towards meaningful learning, in order to uncover ways that enable scientific-chemical knowledge really be built in the school space.